A hedonic wage regression model for vulnerable workers in Malaysia: the use of exclusion restriction as a remedy for self-selection bias - Hazrul Shahiri; Park, Kihong; Zulkifly Osman (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper uses an exclusion restriction variable as the key to resolve an identification problem in self-selection bias of a wage regression model. The study basically utilizes Hedonic Wage Theory (Rosen 1986, 1974) to test the relationship between vulnerable workers and wage. Analysis was made using the Mincerian semi-log earnings function (Mincer 1974) specified in the tradition of Becker’s Human Capital Model (Becker 1964) with a correction for self-selection bias. A total of 1705 private sector employees were selected and the result showed that the coefficient for predicted vulnerable worker variable was significant but non-positive. The implication of this result is that no adjustments in wages are made to compensate workers for undesirable job conditions. A third party, namely government interventions, is therefore needed in order to protect and enhance the well-being of the vulnerable workers.